COMPARISON OF HPV DETECTION USING HC-II METHOD WITH PAP SMEAR SCREENING IN COMMERCIAL SEX WORKERS IN KEDIRI - Erawati Erawati; Puspa Wardhani; Aryati Aryati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Female commercial sex workers are females that have multiple sexual partners and have high risk due to exposure to blood, semen, and vaginal discharge contaminated with microorganisms causing sexually transmitted disease such as infection caused by Human papillomavirus (HPV). This behavior creates a high susceptibility for commercial sex workers in obtaining HPV, which is the leading cause of cervical cancer. Cervical cancer is the most common cancer in females in Indonesia, which is why screening, especially for females with a high risk such as commercial sex workers, must be done. The purpose of this experiment was to compare the detection methods of HPV using Hybrid capture-II (HC-II) in order to find out high risks HPV types (type 16, 18, 31, 33, 35, 39,45, 51, 52, 56, 58, 59, and 68) by Pap smear done in commercial sex workers in Campurejo Kediri Public Health Center. This study was a descriptive observational experiment with a cross-sectional method. The samples of this experiment were 47 female commercial sex workers, whose detection of HPV using HC-II method was done at the Clinical Pathology Laboratory of the Dr. Soetomo Hospital Surabaya, where 32 samples showed positive results (68.1%) and were infected with high-risk HPV and 15 negative results (31.9%), from the Pap smear three samples (6.4%) showed dysplasia (Cervical Intraepithelial Neoplasia/CIN 1) and 44 samples (93.6%) showed normal smears with inflammation or infection in the cervix. Statistically showed a significant difference between the results of HC-II and Papsmear (p=0.000).